APAKAH PANDEMI COVID-19 BERPENGARUH TERHADAP PRODUKTIVITAS PENELITIAN TENTANG PERPUSTAKAAN PADA JURNAL INTERNASIONAL? - Prasetyo Adi (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2021)
Corona virus pandemic restricts public activities. Libraries as information provider can help long-distance learning process due to Corona. Librarians as library operators are demanded to innovate through research and publication. This study aims to analyse if Corona virus pandemic influences productivity of Indonesian authors’ publication in accredited international journal. This study uses quantitative approach with secondary data analysis. Sample for this research are papers/scientific articles published with the keyword or topic “library”, the keyword or topic “information science”, and whose corresponding author is from Indonesia. Results of this research shows that Corona virus pandemic did not significantly influence publication productivity. In addition, scientific article on information science was more preferable than topic on library.